Antiplaque effects and mode of action of a combination of zinc citrate and a nonionic antimicrobial agent - Saxton, C A; Svatun, B; Lloyd, A M (Scandinavian journal of dental research, 1988)
The effect upon plaque growth of adding a nonionic antimicrobial agent, triclosan, to a dentifrice containing zinc citrate was established in short-term in vivo studies. Plaque regrowth was inhibited by brushing with dentifrices which contained either zinc citrate or triclosan. When both were combined in the same dentifrice, the inhibition of overnight plaque regrowth was significantly greater. In two 4-day non-brushing studies, the dentifrices containing both zinc citrate and triclosan were applied either undiluted by the use of a cap splint or as 23% suspensions in water. Both methods resulted in significant reductions in plaque accumulation, with the greater activity being observed for the undiluted application of the dentifrice. Analysis of results of the overnight plaque studies for individual teeth revealed that the two agents had a complementary inhibitory action on plaque regrowth, zinc citrate being more effective on existing plaque whereas triclosan inhibited plaque formation on clean surfaces. The dentifrice containing both agents was effective against both existing plaque and new plaque formation. It is concluded that the addition of triclosan to a dentifrice containing zinc citrate improves its antiplaque potential.